Lebanon Economic Monitor, Fall 2020 : The Deliberate Depression - World Bank (World Bank, Washington, DC, 2020)
The Lebanon Economic Monitor provides an update on key economic developments and policies over the past six months. It also presents findings from recent World Bank work on Lebanon. It places them in a longer-term and global context and assesses the implications of these developments and other changes in policy on the outlook for Lebanon. Its coverage ranges from the macro-economy to financial markets to indicators of human welfare and development.